An Analysis of Service Quality Towards Customer Satisfaction Using Importance Performance Analysis (IPA) Method - Dhea Arghisa; Sulisti Afriani; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to measure the level of service satisfaction provided by Bank Bengkulu Sub-Branch Ipuh to customers, determine the dimensions of service expected by customers (expected) and those received by customers (perceive) and examine the difference (gap) between service quality expected by customers. customers with the quality of service received by customers. This research is a type of descriptive research with a quantitative approach. Descriptive research is research that leads to the disclosure of a problem or situation as it is and reveals an existing fact, although sometimes interpretation or analysis is given. Based on the results of the calculation of the Customer Satisfaction Index (IKP) Bank Bengkulu Ipuh Sub-Branch obtained a total service satisfaction score of 64.64 which is included in the quite satisfactory category. There are 5 dimensions of service quality tested, there is 1 dimension with a satisfactory assessment, namely the dimension of physical evidence (69,76). While the other 4 dimensions, namely reliability (63.20), responsiveness (65.12), assurance (63.04) and empathy (62.40) each received a satisfactory rating. Based on these results, it can be concluded that the level of service quality of Bank Bengkulu Sub-Branch Ipuh is considered satisfactory according to customers of Bank Bengkulu Sub-Branch Ipuh.